Case Report: Subacute cutaneous lupus erythematosus induced by the anti-PD-1 antibody camrelizumab combined with chemotherapy - Bao, Hejing; Zhang, Jiani; Luo, Xi; Song, Xiaojing; Li, Juan; Mao, Nan; Chen, Fang; Bao, Hehong; Hu, Jiazhu; Cao, Xiaolong; Ma, Shudong; Lin, Liping (Frontiers in Immunology, 2025)
The use of immune checkpoint inhibitors (ICI) can lead to immune-related adverse events (irAE), of which skin irAE is common, affecting up to 50% of ICI-treated patients. Although only a few cases of subacute cutaneous lupus erythematosus (SCLE) have been reported in patients receiving anti-programmed death-1(anti-PD-1) immunotherapy, it is important to identify ICI-induced SCLE because it may cause delayed and/or prolonged skin reactions even after treatment discontinuation. To date, no cases of cutaneous lupus associated with Camrelizumab treatment have been reported.Case reportWe report a case of a patient with advanced non-small cell lung cancer (NSCLC) who gradually developed erythematous rashes on sun-exposed skin with pruritus after one course of anti-PD-1 antibody Camrelizumab combined with chemotherapy. The rashes were initially considered as eczema, but did not improve after symptomatic treatment. The rashes continued to worsen after the third course of treatment, and the pruritus was unbearable. After antibody testing, the patient was found to have positive anti-SS-A/Ro antibody, and the histological changes were consistent with subacute cutaneous lupus erythematosus. SCLE was controlled with local and systemic glucocorticoids, hydroxychloroquine, and discontinuation of anti-PD-1 therapy.ConclusionCamrelizumab treatment may be associated with the appearance of subacute cutaneous lupus erythematosus in sun-exposed skin regions, which can be rapidly relieved by local and systemic glucocorticoids and hydroxychloroquine. It is recommended to perform early antibody testing and skin biopsy for diagnosis and treatment. Unlike classic drug-related SCLE, patients may develop multiple autoimmune diseases, and caution should be taken when using immune checkpoint inhibitors for subsequent treatment.